Condom application skills and self-efficacy in youth: A systematic review and meta-analysis. - John L Ferrand; Aaron J Blashill; Heather L Corliss; Eric R Walsh-Buhi (PLoS ONE)
Globally, and in the United States (U.S.) specifically, rates of reported sexually transmitted infections (STIs) have been steadily increasing and are especially high among youth aged 13-25 years. Using condoms correctly and consistently is an effective STI prevention measure for sexually active youth, yet public health endeavors tend to focus only on condom use consistency. Directly measuring condom application is challenging and expensive. Alternative tools evaluate this behaviour, but little evidence exists on the appropriateness of these instruments in measuring application skills. This systematic review and meta-analysis examined the association between condom application skills and self-efficacy. We conducted a search of several databases as well as unpublished works. Studies were included if they were in English, examined youth aged 13-25 years, and were available between 1992 and 2019. The authors screened 630 titles and abstracts for initial inclusion criteria. A full-text review of 30 studies was conducted. The authors included 19 studies in the systematic review and 5 studies were included in the meta-analysis. Both a fixed- and random-effects model (Q = .2321, I2 = 0%) yielded a medium-sized statistically non-significant association (r = 0.217) between skills and self-efficacy. Despite the small sample size, findings suggest that skills and self-efficacy may not be as interchangeable as previously assumed when assessing condom application. Implications for future research are discussed.